IMPLEMENTASI TEORI BEHAVIORISME TERHADAP PEMBIASAAN MEMBACA ASMAUL HUSNA - Nur Arofah (Paedagogia: Jurnal Pendidikan, 2019)
The theory of learning behaviorism observe the change of one's behavior as a result of past experience. This theory emphasizes that the behavior is a result of the interaction between the stimulus and the response. This theory does not recognize the presence of innate intelligence or derivatives, but rather recognizes that intelligence is influenced by environmental factors. This theory can be applied in learning that requires practice, habituation and repetition. Therefore, to introduce and understand about Asmaul Husna, the theory of behaviorism can be applied in the process of habituation. The recitation of Asmaul Husna is very much contained in its role. Among them to introduce and hang students about Asmaul Husna, so students will feel closer to God if they often apply Asmaul Husna readings and will always feel that everything we do is supervised by God. Like the example of one of the traits contained in Asmaul Husna. Based on the discussion, the problem raised is how to implement behaviorism theory to the habituation of Asmaul Husna reading.